PENERAPAN METODE BALANCE SCORECARD SEBAGAI TOLOK UKUR PENILAIAN KINERJA PADA ORGANISASI SEKTOR PUBLIK (Studi Pada Dinas Pajak Daerah dan Pengelolaan Keuangan Kota Yogyakarta) - Yulaikah Yulaikah; Sri Ayem (Jurnal Akuntansi, 2014)
Regional Tax Agency and Financial Management ( DPDPK ) Yogyakarta is one of responsibility center in the structure organizations of local government that have an important role in budget planning and controlling. This study aims to assess the performance of DPDPK during 2009-2012 by using balanced scorecard . Balance scorecard is a performance measurement which is translated into four perspectives of performance, namely: the financial perspective, the perspective of local taxpayers, internal business process perspective and learning and growth perspectives. Data analysis method used is quantitative and qualitative descriptive's analytics. Basedon the analysis of performance measurement DPDPK Yogyakarta used the balanced scorecard method can be concluded that the DPPDK performance during the years of 2009-2012 considered quite good. Thereby the balance scorecard is suitable to be applied to the DPDPK Yogyakarta because it can provide a more structured and comprehensive in all aspects of the performance of both financial and non-financial organizations. Keywords : Performance Measurement, Balanced Scorecard, Public Sector, DPDPK